Lumazine Peptides from the Marine-Derived Fungus Aspergillus terreus - Minjung You (Marine Drugs, 2015)
Terrelumamides A (1) and B (2), two new lumazine-containing peptides, were isolated from the culture broth of the marine-derived fungus Aspergillus terreus. From the results of combined spectroscopic and chemical analyses, the structures of these compounds were determined to be linear assemblies of 1-methyllumazine-6-carboxylic acid, an amino acid residue and anthranilic acid methyl ester connected by peptide bonds. These new compounds exhibited pharmacological activity by improving insulin sensitivity, which was evaluated in an adipogenesis model using human bone marrow mesenchymal stem cells. In addition, the compounds exhibited fluorescence changes upon binding to DNA, demonstrating their potential applications to DNA sequence recognition.